2021
DOI: 10.1161/jaha.121.021417
|View full text |Cite
|
Sign up to set email alerts
|

Newly Diagnosed Atrial Fibrillation in Acute Myocardial Infarction

Abstract: Background It remains controversial whether long‐term clinical impact of newly diagnosed atrial fibrillation (AF) in the acute phase of acute myocardial infarction (AMI) is different from that of prior AF diagnosed before the onset of AMI. Methods and Results The current study population from the CREDO‐Kyoto AMI (Coronary Revascularization Demonstrating Outcome Study in Kyoto Acute Myocardial Infarction) Registry Wave‐2 consisted of 6228 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 28 publications
1
13
0
2
Order By: Relevance
“…3,4 Moreover, once patients with AMI are combined with NOAF, it often means a worse prognosis, which deserves high attention and strengthened management. 2,5,6 The latest literature reported that the incidence of NOAF in AMI patients undergoing emergency PCI was 7.9%, 7,8 but, in elderly patients aged 75 years or older with NSTE-AMI without PCI, it remains unclear how the incidence of NOAF and whether the continuous increase in TnI increases the incidence of atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Moreover, once patients with AMI are combined with NOAF, it often means a worse prognosis, which deserves high attention and strengthened management. 2,5,6 The latest literature reported that the incidence of NOAF in AMI patients undergoing emergency PCI was 7.9%, 7,8 but, in elderly patients aged 75 years or older with NSTE-AMI without PCI, it remains unclear how the incidence of NOAF and whether the continuous increase in TnI increases the incidence of atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%
“…What's more, ST‐segment elevation in 15 leads, especially anterior wall myocardial infarction accompanied by CRBBB (Widimsky et al, 2012), indicated a large infarct area in the anterior wall of the left ventricle. And newly diagnosed atrial fibrillation, caused by simultaneous dysfunction of ventricle and atrium, suggested the four cardiac chambers were affected due to the acute occlusion of multiple coronaries (Obayashi et al, 2021). And, it was confirmed by the echocardiography with an LVEF of 22%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early paroxysmal AF should be reversed as early as possible. Patients with persistent AF should receive regular anticoagulation treatment and, if necessary, interventional therapy may be provided (31,32). Pharmacological conversion is the most traditional and classical treatment for patients with AF for restoring the SR of the heart (33).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early paroxysmal AF should be reversed as early as possible. Patients with persistent AF should receive regular anticoagulation treatment and, if necessary, interventional therapy may be provided ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%